Trajetórias de mulheres negras na educação de crianças pequenas no Distrito do Jaraguá em São Paulo: processos diferenciados de formação e de introdução no mercado de trabalho - Oliveira, Waldete Tristão Farias (2006)
This research has for objective to understand and to reconstruct the professional trajectory of educators who act in day-care centers, at the moment, calls of Centro de Educação Infantil. The investigated citizens are black women - day-care center educators. Life histories had been collected with the objective to understand as the day-care center if it transformed into a market of possible work for the black women, deriving of the social class subordinate. This inquiry counted on the contribution of six professionals who act in day-care centers of the city of São Paulo, specifically located in the zone the northwest of the city under jurisdiction of the Coordenadoria de Educação de Pirituba. Four are assistant of infantile development of direct day-care center and two are managing; one of indirect day-care center and to another one of covenanted day-care center. Leaving of the principle of that "all the lives are interesting", verbal history was used as a strategy to return the word to the day-care center educators so that they spoke of singular moments that they had only known, as well as, on the social place of the professional of the day-care center. The carried through research showed that, for the set of the searched educators, the ingression in the day-care center represented ascending social mobility in relation to its family of origin and that identify was and is (they are) built to the long one of the life for contrast, in the different situations and also for option politics